The effects of genistein supplementation on fructose induced insulin resistance, oxidative stress and inflammation - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Aims: This experimental study was designed to investigate the effects of 10 weeks genistein administration on oxidative stress and inflammation in serum and liver of rats fed with fructose. Main methods: 6-8 weeks old, 40 male Sprague-Dawley rats were included. Group 1 (control) was fed with standard chow food and 100 1/kg/day/rat dimethyl sulfoxide (DMSO) administered subcutaneously; group 2 (genistein) with standard chow food and 025 mg/kg/day/rat genistein; group 3 (fructose) with standard chow food and drinking water 20% fructose, group 4 (fructose + genistein) with standard chow food, drinking water with 20% fructose and 025 mg/kg/day/rat genistein. TNF-alpha, IL-6, visfatin as inflammatory markers and 8-isoprostane as a oxidative stress marker were measured by ELISA, glucose, triglyceride, total cholesterol, LDL-cholesterol and HDL-cholesterol by enzymatic calorimetric method, AST and ALT by kinetic UV method. Key findings: Significantly high 8-isoprostane levels in serum (p < 0.001) and liver (p < 0.05) in group 3 compared to control group indicate that presence of oxidative stress. Significantly high TNF-alpha and IL-6 levels in serum (p < 0.05) and liver (p < 0.01) and visfatin levels in serum (p < 0.001) of group 3 indicate inflammation accompanying insulin resistance and oxidative stress. Genistein administration to fructose group causes a significant decrease in HOMA-IR (p < 0.001) and LDLC (p < 0.05) level. Significantly lower serum 8-isoprostane (p < 0.01) level indicates the antioxidant effect of genistein and significantly lower liver TNF-alpha (p < 0.01), serum, liver IL-6(p < 0.01) and serum visfatin (p < 0.01) levels reflect the antiinflammatory effects of genistein. Significance: Genistein administration to rats fed with fructose causes an ameliorating effect on HOMA-IR values and lipid status markers in addition to its antioxidant and antiinflammatory effects. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Genistein; Fructose; Insulin resistance; Inflammation; Oxidative stress; TNF-alpha; IL-6; Visfatin 8-isoprostane; INDUCED DIABETIC-RATS; POSTMENOPAUSAL WOMEN; RENAL INFLAMMATION; ENDOTHELIAL-CELLS; ENZYME-ACTIVITIES; MOUSE MODEL; SOY; MICE; ISOFLAVONE; GLUCOSE